: - Deva Yulinda; Suci Ramadhani Putri (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2023)
This article aims to find out how the stereotyping of housewives as unemployed women in the Population and Civil Registration Service (Dukcapil) of North Lombok Regency (KLU) and how to gender analysis of this. This research is qualitative research that aims to describe various stereotypical problems towards housewives using a gender analysis approach. This research was conducted at Dukcapil KLU. This article argues that stereotyping of housewives is a form of embodiment of the theory of "State Ibuism" by Julia Suryakusuma, which in fact is also rooted in state administration, particularly in population documents published by Dukcapil. Analyzing it using the theory of State Ibuism, it is known that the KLU community is shackled by the notions of "ibuism" and "housewifization". The understanding of "motherism" is reflected through husbands who think that their wives are better off just staying at home and not working. Meanwhile, the notion of " housewifization" is reflected through stereotyping of the status of a job taking care of the household is the same as being unemployed, because the job of taking care of the household is considered to have no economic value.